Preoperative chemoradiation in adenocarcinoma of the pancreas. A single centre experience advocating a new treatment strategy. - Golcher, H; Brunner, T; Grabenbauer, G; Merkel, S; Papadopoulos, T; Hohenberger, W; Meyer, T (2008)
AIMS: To evaluate a single centre's experience with pancreatic carcinoma focused on preoperative chemoradiation therapy (CRT) for treatment of locally advanced pancreatic carcinoma. The aim of the present analysis was to evaluate the median overall survival time (OS) after preoperative CRT and to compare it with OS after primary resection of pancreatic carcinoma. In conclusion a new treatment strategy was developed using multimodality treatment for pancreatic carcinoma deemed to be resectable by CT-scan. PATIENTS AND METHODS: Between 1995 and 2003, 302 patients with ductal adenocarcinoma of the pancreatic head and body were recorded prospectively and OS was analysed with regard to therapy. RESULTS: Fifty-eight patients were resected without any pretreatment and had an OS of 21 months. Twenty-one patients with initially unresectable tumours underwent CRT followed by resection and had an OS of 54 months, which was not significantly different from primary resection (p=0.315). Lymph node metastasis was significantly reduced after CRT (p=0.0029). OS for patients whose tumours could not be resected was 3-10 months, depending on tumour stage and consecutive therapy. CONCLUSION: CRT pretreatment was effective in locally advanced pancreatic carcinoma and resulted in resection of tumours otherwise staged as non-resectable. This experience led to a randomized trial for patients who by CT are staged to have resectable cancer of the pancreatic head with the intent to increase curative resectability and survival by neoadjuvant CRT (ISRCTN78805636/NCT00335543).